SIMETRISITAS SEBAGAI KOSMOLOGI RUANG JAWA PADA RUMAH KOLONIAL DI KAMPUNG BUBUTAN SURABAYA (The Symmetricity of Colonial House as Javanese Space Cosmology at Kampung Bubutan Surabaya) - Cahyani, Risqi; Wulandari, Lisa Dwi; Antariksa, Antariksa (Tesa Arsitektur, 2014)
Symmetricity is part of the Javanese Cosmology that describes the perfection of Javanese. Symmetricity has been the main principle in Javanese house, not only in the faÃ§ade of the house but olso the hierarchy of spatial inside. Kampung Bubutan is the ancient settlement experienced two phases of Government which strongly influenced the architectural character, which at the time became the Kingdom of Mataram (15th century) and the colonialism of the Netherlands (17th century up to the 19th century). The remains of the era of colonialism in Surabaya can still be felt by many colonial buildings surounding in the settlement. This study will explore how the principles of Javanese symmetricity in Kampung Bubutan colonial house, by using descriptive â qualitative methods. Can the Javanese symmetricity still become principal in colonial house and survive? The results shows that the symmetricity of fasade became decreased at the last peroide of 19th century, when the NA-Romantiek was popular. Spatial symmetricity at the colonial houses have inconsistancy since the beginning of 19th century until the early 20th century. The main hierarchy of the spatial Javanese House, which are pendopo (verandah), pringgitan (foyer), dalem (living room) and senthong (bedroom), have become inconsistence since the end of 19th century periode